Avaliação diferencial do déficit cognitivo em idosos - Thiago Henrique Ferreira Vasconcellos (2014)
This dissertation is made up of two studies. The first is intended to analyze psychometric characteristics of the Rey Complex Figure Test (RCF) and Rey Auditory Verbal Learning Test (RAVLT) to assess episodic memory and, susidiarily, short-term memory, in which the short-term memory test (STM) from the cognitive processing battery was used. The sample included 240 people residing in the town of Patos de Minas, Minas Gerais. Most of them were female, (85.00%), aged from 40 to 87 (m=66.29, dp=10.66) and averaging of 6.3 years of education (dp=3.99). The tests employed showed strong internal consistency: RCF (Cronbachs alpha 0.98), RCF (Cronbachs alphas = 0.84-0.85), RAVLT (Cronbachs alpha = 0.86-0.99) and are explained by three latent variables (visual memory, episodic memory and intrusions). The model generated by the confirmatory factor analysis shows an adequate degree of data adjustment (X2 = 34.26, df = 24, CFI = 0.98, RMSEA = 0.06). The second study in this dissertation is intended to propose four models that define different theses on the effect of aging on the cognitive skills of the processing, inductive reasoning and episodic memory system, namely: shared influence, mediated influence, cascade mediation and cascade. Factor scores of cognitive processing battery (CPB), raw scores of inductive reasoning development test (IRDT), and raw scores of delayed recall (A7), verbal learning (AV), retroactive interference (IntR) of the Rey Auditory Verbal Learning Test (RAVLT), and age were used as variables. The cascade model displayed the best data-matching level (X2 = 48.38, df = 39, CFI = 0.98, RMSEA = 0.03), so age favors drops in episodic memory performance and has no causal or correlational effect on processing and inductive reasoning basic skills.